2018
DOI: 10.1093/gigascience/giy019
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequences of 89 Chinese sheep suggest role of RXFP2 in the development of unique horn phenotype as response to semi-feralization

Abstract: BackgroundAnimal domestication has been extensively studied, but the process of feralization remains poorly understood.ResultsHere, we performed whole-genome sequencing of 99 sheep and identified a primary genetic divergence between 2 heterogeneous populations in the Tibetan Plateau, including 1 semi-feral lineage. Selective sweep and candidate gene analysis revealed local adaptations of these sheep associated with sensory perception, muscle strength, eating habit, mating process, and aggressive behavior. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 56 publications
(62 reference statements)
9
86
1
Order By: Relevance
“…More importantly, relaxin-like receptor 2 (RXFP2) gene was harbored in this genomic region. The ROH hotspot region also overlapped the selective signatures in RXFP2 across many sheep breeds [27,32,[45][46][47][48]. GWAS results demonstrated that RXFP2 region was associated with horn phenotype in sheep [49].…”
Section: Discussionmentioning
confidence: 80%
“…More importantly, relaxin-like receptor 2 (RXFP2) gene was harbored in this genomic region. The ROH hotspot region also overlapped the selective signatures in RXFP2 across many sheep breeds [27,32,[45][46][47][48]. GWAS results demonstrated that RXFP2 region was associated with horn phenotype in sheep [49].…”
Section: Discussionmentioning
confidence: 80%
“…By contrast, in Southeast Asia, shattering in weedy rice is caused at least in part by adaptive introgression of wild alleles at sh4 [98]. Finally, in feral chickens and sheep [50,51], genome scans found only limited overlap between outlier loci (i.e., candidate 'feralization loci'), and genome regions that are known to have evolved under domestication. Altogether, these examples show that, at the genetic level, domestication-related changes are not predictably reversed by feralization.…”
Section: How Do Gene 3 Environment Relationships Influence Feralization?mentioning
confidence: 96%
“…Several methods are available for assessing how admixture affects fitness in feral populations, including: (i) direct measurements of growth, survival, reproduction, and health in hybrids; (ii) functional analyses of outlier loci detected in genome scans (e.g., [50,51]); and (iii) experimental tests of the effects of these loci in laboratory systems (e.g., [50]). In recipient wild populations of fish, these approaches often find outbreeding depression (e.g., [52,53]).…”
Section: Fitness Consequences Of Admixturementioning
confidence: 99%
“…We downloaded a total of 52 sheep whole-genome sequencing data including 20 fattailed sheep of two breeds from Xinjiang, China, 15 improved thin-tailed sheep of seven breeds from Europe and 17 wild Mouflon sheep (Ovis orientalis) from the Middle East (Additional file 1: Table S1) [43,44]. Selective sweeps between these thin-or fat-tailed sheep breeds and Mouflon sheep populations were scanned using a genome-wide sliding window strategy based on the SNPs with less than 10% missing data [45].…”
Section: Selective Sweeps Analysismentioning
confidence: 99%